1990
DOI: 10.1111/j.1365-3059.1990.tb02499.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes of Phytophthora infestans collected in England and Wales from 1985 to 1988: mating type, response to metalaxyl and isoenzyme analysis

Abstract: In a survey of 1864 isolates derived from samples of Phytophthora infestans obtained from potato and tomato collected in England and Wales between 1985 and 1988, the A2 mating type was identified in approximately 10% of samples. There was no evidence for an overall increase in the frequency of the A2 mating type over this period. In agar culture, A2 isolates exhibited a distinct lumpy‐colony morphology. Lumps were made up of intensely dichotomously branched hyphae. The incidence of resistance to metalaxyl amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 17 publications
0
27
0
1
Order By: Relevance
“…In addition, no evidence of 'mixed' cultures or self-fertile isolates was obtained. Other researchers have also found that epidemics in a particular location are generally caused by single mating type populations (2,14,27,32,50), although mixed populations sometimes occur (5,34,36,44,48). Therefore, the VOLUME 20, 1998 opportunities for sexual reproduction still appear to be limited in Canada, except possibly in B.C.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, no evidence of 'mixed' cultures or self-fertile isolates was obtained. Other researchers have also found that epidemics in a particular location are generally caused by single mating type populations (2,14,27,32,50), although mixed populations sometimes occur (5,34,36,44,48). Therefore, the VOLUME 20, 1998 opportunities for sexual reproduction still appear to be limited in Canada, except possibly in B.C.…”
Section: Discussionmentioning
confidence: 90%
“…Some authors have recognized an intermediate category (12,14,43,44), while others have not (31,37,38). However, the range of metalaxyl response within a group of isolates classed as resistant has often been great (41).…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis states that the A2 mating type arose from the Al mating type either through mutation or mitotic recombination (Shattock et al, 1990). According to Shaw (1983) mating type is coded for by one gene with two alleles.…”
Section: The A2 Mating Type In Europementioning
confidence: 99%
“…No A2 was recorded from the terai ( Table 1) and none of the isolates tested was self-fertile. All A2 isolates exhibited a distinct colony morphology and lumpiness in Rye A agar as did those observed by Shattock et al (1990). Such lumpiness was due to aggregation of dichotomously branched aerial hyphae.…”
Section: Resultsmentioning
confidence: 75%